Protocol group education for family caregivers of elderly dependents - Cristina Anguita Carpio; Gemma María Carpio Colomo (Fundación para el Desarrollo de la Enfermería, 2012)
Family is the main care source for the dependent person. The act of looking after somebody, involves the development of multiple tasks, apart from spending a lot of time. This implies a series of requirements that would be able to damage the family caregivers' quality of life, and definitively, their health. Objetive: training for family caregivers to provide quality care, in order to succeed in this project, we establish three specific aims: improving the information and training, increase self-care abilities and focus on resources and support services for informal caregivers. Methods: We are going to implement an educative intervention in a group of 12 informal caregivers of people over 65 years, dependent on chronic diseases and develop home care. The program will be composed of 10 sessions, each one of two-hour-long. The first session will consist of an introduction and the last session will be reserved to solve doubts and to deal with the assessment of the program. Throughout the rest of sessions, contents about training, self, resources and assistance services for caregivers will be proposed. In order to evaluate the efficiency of the program, a multiple choice questionnaire will be taken both al the beginning and at the end of the different sessions. In order to evaluate the human resources and the applied methodology, another questionnaire will be passed.